EFFECTIVE WAYS OF ORGANIZING METHODOLOGICAL SERVICE IN SCHOOL EDUCATIONAL ORGANIZATIONS - Karshibaeva Dilfuza Khidirbaevna (American Journals Publishing, 2023)
In the article in the organization of preschool education organization of methodical service and important duties of a methodist are discussed. Information about the task, main directions and principles of methodical service is also provided. Recommendations on the effective use of various approaches, forms and tools in the organization of methodical service are given.
Keywords: methodist, methodical service, plan, activity, perspective, psychological environment, innovation, technology, democracy, innovative initiative, didactic, variant approach, pedagogical council, best practice, skill, dispute, discussion, work game.